Service Evaluation of the Impact of Capnography on the Safety of Procedural Sedation - Corbett, Gareth; Pugh, Peter; Herre, Jurgen; See, Teik Choon; de Monteverde-Robb, David; Torrejon Torres, Rafael; Saunders, Rhodri; Leonard, Catherine; Prakash, Amit (Frontiers in Medicine, 2022)
Background: Capnography has been associated with a reduced incidence of events related to respiratory compromise during procedural sedation. Methods: A prospective service evaluation was conducted at a large United Kingdom (UK) teaching hospital to assess the impact of capnography on patient safety within four speciality services: bronchoscopy, endoscopy, interventional cardiology, and interventional radiology. Events were defined as provided by the World Society of Intravenous Anaesthesia. 1,401 patients were enrolled in the evaluation, with 666 patients before and 735 after implementation of capnography. Data was entered as a convenience sample on site in an offline data-collection tool. Results were assessed for the relative reduction in the incidence and resulting adjusted odds ratio for the combined incidence of oxygen desaturation (75-90% for <60s), severe oxygen desaturation (<75% at any time) or prolonged oxygen desaturation (<90% for >60s), bradycardia (>25% from baseline) and tachycardia (>25% from baseline).selected adverse events. The adjusted odds ratio was controlled for both procedure and patient characteristics. Results: After implementation of capnography, a significant reduction (43.2%, p ≤ 0.05) in adverse events was observed: 147 adverse events occurred during 666 procedures without capnography compared with 93 adverse events that occurred during 735 procedures with capnography. The adjusted odds ratio for the occurrence of the target adverse events was 0.57 [95% CI: 0.42 – 0.77]. Multivariable linear regression indicated that capnography was a significant predictor (p<0.001) of reduced adverse events. Conclusion: These results suggest improved patient safety following capnography implementation.